(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Research on the ability to marriage in the acatholic matrimony in Spain ABSTRACT: The current regulation of religious minorities in Spain requires obtaining a certificate of matrimonial capacity. This certification necessitates the prior preparation of a file that demonstrates the marital suitability of the prospective spouses. This work presents and evaluates a line of research that confronts positive law with state institutions related to the subject, from a pragmatic perspective. It is a study, from 1992 to the present, on the legal sources affecting the preliminary file and the certificate of capacity, focusing on registry regulations and their practice, through the statements made by the General Directorate of Legal Security and Public Trust, along with the contributions from scientific doctrine, this will provide an in-depth view of the subject. SUMARIO: 1. Introducción - 2. La regulación legal del matrimonio de las minorías religiosas en España. Antecedentes - 2.1. Momento de vigencia de la eficacia civil - 2.2. La exigencia de un certificado de capacidad en la redacción originaria de los Acuerdos - 2.3. La interpretación administrativa posterior - 2.3.1. La Instrucción de 10 de febrero de 1993 - 2.3.2. Ámbito territorial - 2.3.3. Ámbito personal - 2.3.4. El expediente previo - 3. La regulación vigente y su repercusión en el certificado de capacidad de los matrimonios de las minorías religiosas - 4. Algunas consideraciones en torno al expediente previo y el certificado de capacidad matrimonial y su incidencia en las Resoluciones de la Dirección General de Seguridad Jurídica y Fe Pública - 4.1. Ligamen, poligamia y expediente previo - 5. Consideraciones finales.